2020
DOI: 10.1016/j.ast.2020.106355
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of robust optimization for design of rotorcraft airfoils in forward flight

Abstract: The paper compares the deterministic and robust approaches to improve the aerodynamic design of helicopter airfoils. The two formulations are different due to the characteristics of each approach. In the deterministic case, the objective of optimization is the minimization of drag while maintaining a level of lift that guarantees satisfaction of trimming condition. In the case of robust design, a range of angles of attack and not a single trim condition is considered. Thus, the robust optimization takes the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Geleneksel yöntemlerde sabit uçuş koşulları kullanılarak optimizasyon gerçekleştirilmektedir [7]. Fakat tasarımcının kontrol edebildiği veya kontrol edemediği durumlardan ötürü sabit kabul edilen uçuş koşullarında farklılıklar oluşmaktadır [16]. Bu durum da çözüm üretilen problem için belirsizliklerin oluşmasına sebebiyet vermektedir.…”
Section: Giriş (Introduction)unclassified
“…Geleneksel yöntemlerde sabit uçuş koşulları kullanılarak optimizasyon gerçekleştirilmektedir [7]. Fakat tasarımcının kontrol edebildiği veya kontrol edemediği durumlardan ötürü sabit kabul edilen uçuş koşullarında farklılıklar oluşmaktadır [16]. Bu durum da çözüm üretilen problem için belirsizliklerin oluşmasına sebebiyet vermektedir.…”
Section: Giriş (Introduction)unclassified
“…Most of the published literature on airfoil optimization deal with the problem of maximizing airfoil performance at a given flight condition. Fusi et al 23 compare the deterministic and robust optimization approaches to improve the aerodynamic design of helicopter airfoils with the goal of maximizing their lift to drag ratio. The robust approach shows the capability to reach the same mean performance of the deterministic one, but with a lower degradation of performance in other conditions considered through the uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed in several works that MFMBO can reduce significantly the computational cost while keeping a satisfactory accuracy. [17][18][19][20] For instance, Gano et al 19 showed that MFMBO can save resources by 60%; Park et al 21 reported a cost saving of 86%. When analyzing MFMBO studies, we find that this treatment is related to three factors, namely, the type of fidelity, the multi-fidelity model, and the MFMBO strategy.…”
Section: Introductionmentioning
confidence: 99%